Queuing theory-based innovation diffusion modelling incorporating change in adoption rate. (2018) - Anand, Adarsh; Agarwal, Mohini; Aggrawal, Deepti; Singh, Ompal
Adoption has always been an important process to discuss among marketers. Major work in the field of innovation adoption has been based on theory of first purchase by consumers. Of late attention has also been given to multi-stage nature of diffusion process. There are practitioners who have verified adoption as multi-stage process (depending on awareness and motivation). Researchers have lately also understood the value of change in marketing strategy and other factors that often lead to change in the rate of adoption. In this paper, we have made use of this stage wise approach of market penetration along with change point concept, have developed a methodical approach based on infinite server queuing theory and predicted sales for consumer durables. Experimental results estimated on sales of two different consumer durables show that present proposal can depict the change in adoption rates and predict the behaviour of the product in more accurate manner.